PENGARUH PEMBERIAN JERUK NIPIS (CITRUS AURANTIFOLIA (Chrism.) SWING) TERHADAP KADAR TRIGLISERIDA DAN BERAT BADAN TIKUS PUTIH (RATTUS NORVEGICUS) JANTAN GALUR WISTAR - Djohari, Meiriza; Rahmi, Yuni (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
The research about the effect of lime (Citrus aurantifolia (chrism.) Swing) to levels of triglycerides and body weight of male rats (Rattus norvegicus) wistar strain at a doses of 1.5, 3 and 4.5 ml/kg body weight has done. This study conducted on five groups consisted of norml control , negative control (-), dose of 1.5; 3 and 4 ml/kg body weight, each group consisted of 5 rats , The normal control group were given regular feed, control (-) was given 2 ml cow's brain and regular feed then the test group were given lime each with a dose of 1.5, 3 and 4.5 ml / kg body weight was added with 2 ml of cow's brain and regular feed. The method of measurement used is Enzymatic Colorimetric Test GPO (Glycerol-3-Phosphate Oxidase) at a wavelength of 546 nm. The results showed that administration of lime doses of 3 and 4.5 ml/kg body weight have a significant difference (p <0,05) to the control (-). However, at a dose of 4.5 ml/kg body weight more effectively and more quickly lowering triglyceride levels because the first measurement time of the second measurement time already showed a significant difference (p<0,05) .